The representation of Arab Women in English-Language newspapers: a comparative analysis of Arab and Western media post-Arab spring - Bushra Khalaf Edam,; Azianura Hani Shaari,; Ashinida Aladdin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the portrayal of Arab women in both Arab and Western newspapers in the aftermath of the Arab Spring. It aims to uncover concealed ideologies, concepts, and beliefs held by Arab and Western societies regarding Arab women. Employing Fairclough's three-dimensional Approach to Discourse Analysis as a theoretical framework, the analysis considers the dimensions of discourse fragment (text), discursive practices, and the power dynamics inherent in discourse. Additionally, the study adopts a qualitative approach for collecting and analysing the selected data. Four prominent newspapers, namely the Washington Post, Daily Mail, Arab News, and Gulf Times, were chosen for the study. The findings reveal notable disparities in the depiction of Arab women in Arab and Western media. In Arab newspapers, Arab women are often portrayed as empowered, respected, skilled, educated, and capable contributors to economic and social life. They are occasionally depicted as businesswomen and leaders. Conversely, some Western media tend to portray Arab women as oppressed, subjugated, veiled, plagued by inequality, hidden from view, and restricted by religious rules concerning marriage and dress. They are even referred to as literal odalisques. The study concludes that these varied depictions stem from distinct ideologies prevalent in Arab and Western media. The insights derived from this research regarding the diverse portrayals of Arab women and the influence of different ideologies in Arab and Western media can be valuable for academics, government officials, and community organizations seeking innovative perspectives on women's media representation and active participation in society.